Microcosting analysis of percutaneous coronary intervention with and without intracoronary imaging in an Irish tertiary referral centre - Catherine McGorrian; James F O’Mahony; Ivan P Casserly; Rory A Gallen; Karen M Kuntz; Gavin J Blake (Open Heart)
Background Percutaneous coronary intervention (PCI) is a well-established treatment for coronary artery disease, one of the most significant causes of morbidity and mortality worldwide. Intracoronary imaging, including intravascular ultrasound (IVUS) and optical coherence tomography (OCT), has been shown to improve outcomes for patients following PCI by reducing complications and the need for repeat procedures. Uptake remains highly variable, in part due to concerns over up-front costs.Aim The purpose of this micro-costing analysis was to establish the costs and resource implications of PCI with and without intracoronary imaging.Methods The costing model considered costs associated with the index procedure and related hospital admission and was designed using data obtained from primary data collection, previously published literature and expert opinion. Unit costs were established through communication with the hospital finance department and industry representatives and were reported in 2024 euro. Costs were categorised as staffing, capital and consumables. Staffing costs were calculated in accordance with local guidelines. Capital costs were averaged over a 10-year period. A sensitivity analysis was conducted to assess the impact of the use of IVUS and OCT during PCI.Results The use of intracoronary imaging extends the average procedure time from 45 min to 60 min. The total procedural cost of PCI without intracoronary imaging was €3082. The incremental cost with intracoronary imaging was €752 for IVUS and €884 with OCT.Conclusion This study provides robust data on the cost drivers of PCI with intracoronary imaging in Ireland which has not previously been described. This framework may be of use to finance departments and physicians alike when seeking to establish the cost and resource implications of future modifications to PCI procedures, such as the description of the impact of intracoronary imaging in this study.